THE EFFECT OF NON-ACADEMIC BOOK READING HABITS ON STUDENT CREATIVITY (INTERNATIONAL SEMINAR, 2024)
The influence of reading non-academic books on students' creative abilities has become an increasingly interesting topic in educational research. This study aims to explore how the habit of reading non-academic materials contributes to the enhancement of creativity among university students. Using the literature review method, this study synthesized findings from previous research to examine the relationship between reading frequency, types of books read, and the resulting creative outcomes. The analysis revealed that engaging with diverse genres of non-academic literature, such as fiction, biographies and essays, can foster imagination, divergent thinking and problem-solving abilities. In addition, the research also highlighted the role of reading as a leisure activity that stimulates cognitive flexibility and broadens perspectives. The findings suggest that incorporating non-academic reading into the educational framework can support students' creative development. However, limitations in existing research call for further empirical research to strengthen the theoretical foundation.